Factors Associated with Sick Building Syndrome (SBS) Symptoms in Padang City Hall Office Employees - Nabilla Fitriyani Hasanah; Fadillah Ulva; Febry Handiny (Alifah Health Science Symposium Proceeding, 2023)
Based on data from the World Health Organization (WHO) in 2015, it is known that 30% of new buildings in the world cause symptoms of Sick Building Syndrome (SBS) in workers related to indoor air quality. Based on various research studies in 2008 said that the prevalence of Sick Building Syndrome (SBS) from 18 companies in DKI Jakarta reached 50% in employees. The purpose of the study was to determine the factors associated with SBS symptoms in Padang City Hall Office employees in 2023. This type of research is quantitative with a cross sectional study design. The research was conducted in March - August 2023. The population in this study were all employees of the Padang City Hall office totaling 282 people, while the sample was 129 respondents. The sampling technique is Cluster Random Sampling. The instruments used were questionnaires, thermohygrometers, and luxmeters. Data were analyzed univariately and bivariately. This analysis was carried out with the chi-square test. The results showed that 55% of respondents had SBS symptoms, 25.6% of respondents had smoking habits, 32.6% of respondents had a history of allergies, 15.5% of respondents worked at room temperatures that did not meet the NAB, 70.5% of respondents worked at room lighting levels that did not meet the NAB. There is a significant relationship between allergy history (p=0.005) and temperature (p=0.028) with SBS symptoms. There is no significant relationship between smoking habits (p=0.558), the level of lighting (p=0.028) and SBS symptoms. SBS symptoms are influenced by several factors, namely allergic history and temperature. It is recommended for office employees to make sure to drink enough water to avoid dehydration, chapped lips and dry skin. It is recommended to the building manager to make a smoke-free area. Conduct empowerment for employees to be able to improve the cleanliness of the work environment, use floirescent type lamps for offices.